Some synergetic aspects of education - Pyragas, Kazimieras; Borodinienė, Angelė (Pedagogika, 2014)
Modern synergetic ideas in educational systems are discussed and studied. It is worth noting that although synergetic ideas in educational systems are widely discussed and used in foreign educational literature there is no widespread discussion of these ideas in Lithuania. There are only fragmented mentionings on an idea level or seperate applications of these ideas (Birgelytė, 2005, 2006; Pyragas, Borodinienė, 2011). The purpose of this article is to introduce Lithuanian pedagogues to the main synergetic ideas and their applications in the educational systems. On the other hand there is an urge to take a broader look at the synergetic problems in education in search of new ideas in pedagogy. By taking and justifying a working paradigm that education in the society makes a system (synergetic) we open new horizons to study educational problems and apply new educational methodologies. One of the main problems of the spreading of synergetic ideas in educational systems, the adaptation of complex synergetic concepts and methodology, which were formed in physics, chemistry and mathematics, for humanitarian and social sciences, was discussed.